Exploring Key Factors Affecting Employee Performance: Evidence from Indonesia’s State-Owned Port Enterprises - Amaliah Robhiatul Adawiyah; Catharina Louise Winanda; Agustian Budi Prasetya (Journal Research of Social Science, Economics, and Management, 2025)
This research investigates the impact of the work environment, perceived organizational support, and digital capability on employee performance with motivation acting as a mediating variable. Utilizing a structural equation modeling (SEM) approach, the research examines data collected from employees at state own port enterprise in Java and Lampung province. Findings reveal that digital capability positively influences both employee performance and motivation, work environment directly impacts employee performance only when mediated by motivation. Interestingly, perceived organizational support shows no significant effect on either employee performance or motivation. These results underscore the critical role of digital capability in enhancing employee motivation and performance, suggesting that port enterprise should prioritize digital investments to sustain business operations and achieve higher employee productivity. Digital capability refers to the ability of companies and employees to use digital technologies effectively to improve performance, productivity and innovation. The research contributes to the existing literature by providing new insights into the dynamics of work environment and perceived organizational support within the context of digital transformation in state own port enterprise.